2014
DOI: 10.1159/000358489
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone Furoate Inhibits Cytokine Secretion from Nasal Epithelial Cells and Reduces Eosinophil Survival in an in vitro Model of Eosinophilic Inflammation

Abstract: Background: Fluticasone furoate (FF) is an intranasal corticosteroid indicated for the treatment of allergic rhinitis (AR). However, the anti-inflammatory effects of FF in the nasal mucosa have yet to be investigated thoroughly. The aim of this study was to investigate the effect of FF on eosinophil survival and cytokine secretion from nasal mucosa epithelial cells. Methods: Epithelial cells obtained from nasal mucosa were stimulated with 10% fetal bovine serum (FBS) in the presence of FF (from 10-12 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…In the present study, the corticosteroid FP and the formulation MP-AzeFlu reduced IL-6 and GM-CSF secretions from nasal mucosa epithelial cells relative to FBS. This is consistent with previous findings for the intranasal corticosteroids budesonide, beclomethasone dipropionate, mometasone furoate, FP, and fluticasone furoate [23, 24, 29, 30, 35]. In this study, MP-AzeFlu findings for IL-8, GM-CSF, and sICAM-1 differed little from FP alone.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the corticosteroid FP and the formulation MP-AzeFlu reduced IL-6 and GM-CSF secretions from nasal mucosa epithelial cells relative to FBS. This is consistent with previous findings for the intranasal corticosteroids budesonide, beclomethasone dipropionate, mometasone furoate, FP, and fluticasone furoate [23, 24, 29, 30, 35]. In this study, MP-AzeFlu findings for IL-8, GM-CSF, and sICAM-1 differed little from FP alone.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, MP-AzeFlu findings for IL-8, GM-CSF, and sICAM-1 differed little from FP alone. We also found that FP and MP-AzeFlu reduced eosinophil survival relative to HECM, consistent with previous findings for intranasal corticosteroids [24, 29, 30].…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, Mastruzzo et al reported a decreased number of eosinophils in NP tissue after an 8‐week treatment with budesonide. These observations are expected because it is well known that CS reduces the infiltration and survival of eosinophils by inducing apoptosis and by inhibiting the response to survival signals such as interleukin 5 and granulocyte/macrophage colony‐stimulating factor…”
Section: Discussionmentioning
confidence: 91%
“…Epithelial generated cytokines act as chemoattractants and recruit effector cells such as eosinophils, basophils and T cells to the nasal mucosa. Treatment with fluticasone propionate or fluticasone furoate significantly reduced levels of GM-CSF, IL-6 and IL-8 in stimulated nasal epithelial cells (Ohnishi et al, 1994; Smith et al, 2002; Mullol et al, 2014). In stimulated murine mast cells, fluticasone propionate was shown to inhibit the release of IL-4, IL-6, IL-8 and TNF-α at an IC 50 of <1 nM (Fuller et al, 1995).…”
Section: Intranasal Steroidsmentioning
confidence: 99%